1980
DOI: 10.1051/rphysap:019800015060119300
|View full text |Cite
|
Sign up to set email alerts
|

Low energy neutral beam production by laser vaporization of metals

Abstract: We have quantitatively studied the production of low energy (0.1-10 eV) metal neutral beams by laser vaporization of thin metal foils. For the experimental geometry available on the TFR tokamak, this technique results in the injection of 1015 neutrals in a time of ∼ 300 μs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Laser blow-off has been discussed as a source for 1-10 eV atoms for the first time in the seventies [13][14][15]. A laser blow-off source consists of a laser and a substrate which is transparent for the laser wavelength.…”
Section: Measurement Principlementioning
confidence: 99%
“…Laser blow-off has been discussed as a source for 1-10 eV atoms for the first time in the seventies [13][14][15]. A laser blow-off source consists of a laser and a substrate which is transparent for the laser wavelength.…”
Section: Measurement Principlementioning
confidence: 99%
“…Various metals have been used in previous and current experiments such as iron [7,12,15] and titanium [2]. Aluminum has been used as an LBO tracer element at various experiments [3,[11][12][13]15] and a thorough characterization is documented by the laser blow-off system that was designed for use on the French Tokamak TFR [2].…”
Section: Estimate Of Neutral Ionization Locationmentioning
confidence: 99%
“…Various metals have been used in previous and current experiments such as iron [7,12,15] and titanium [2]. Aluminum has been used as an LBO tracer element at various experiments [3,[11][12][13]15] and a thorough characterization is documented by the laser blow-off system that was designed for use on the French Tokamak TFR [2]. Aluminum was chosen for HSX because it radiates sufficiently to provide a bright photodiode signal at HSX electron temperatures and density, even in low concentrations.…”
Section: Estimate Of Neutral Ionization Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of the resulting ablation plume is also complex, as it is sensitive to the environment under which the ablation is conducted. For this reason, most of the previous studies that reported on the generation of neutral atomic species, such as sodium, 16 aluminum, 17 and indium 18 atoms, using the laser ablation method were typically performed under low-pressure environments to reduce the impact of gas collisions on the resulting plumes. Hence, insufficient information is available from the literature to assess its potential to be used to seed carrier gas at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%